2011
DOI: 10.4236/jbnb.2011.225059
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biotinylated PAMAM Dendrimer Toxicity in Models of the Blood Brain Barrier: A Biophysical and Cellular Approach

Abstract: The interaction of biotinylated G4 poly (amidoamine) (PAMAM) dendrimer conjugates and G4 PAMAM dendrimers with in vitro models of the blood brain barrier (BBB) was evaluated using Langmuir Blodgett monolayer techniques, atomic force microscopy (AFM) and lactate dehydrogenase measures of cell membrane toxicity. Results indicate that both G4 and G4 biotinylated PAMAM dendrimers disrupt the composition of the liquid condensed (LC) and liquid expanded (LE) phases of the 1,2-dipalmitoyl-sn-glycero-3-phosphocholine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…Mukherjee et al suggest this difference can be explained by different intrinsic antioxidant levels of both cell lines, as estimated by intracellular reactive oxygen species assays. 44 Higher cytotoxicity also was observed for biotinylated compared with nonbiotinylated G4 PAMAM dendrimers by a lactate dehydrogenase release assay performed with the bEnd.3 immortalized murine brain capillary endothelial cell line, but not with normal keratinocytes, by Bullen et al 45 The authors investigated the permeability of the blood-brain barrier for the delivery of therapeutic drugs to the brain by means of biotinylated PAMAM dendrimers, as biotin has been shown to cross the barrier through carrier-mediated endocytosis. The blood-brain barrier creates a permeability barrier caused by tight junctions of specialized brain capillary endothelial cells building brain capillary walls.…”
mentioning
confidence: 99%
“…Mukherjee et al suggest this difference can be explained by different intrinsic antioxidant levels of both cell lines, as estimated by intracellular reactive oxygen species assays. 44 Higher cytotoxicity also was observed for biotinylated compared with nonbiotinylated G4 PAMAM dendrimers by a lactate dehydrogenase release assay performed with the bEnd.3 immortalized murine brain capillary endothelial cell line, but not with normal keratinocytes, by Bullen et al 45 The authors investigated the permeability of the blood-brain barrier for the delivery of therapeutic drugs to the brain by means of biotinylated PAMAM dendrimers, as biotin has been shown to cross the barrier through carrier-mediated endocytosis. The blood-brain barrier creates a permeability barrier caused by tight junctions of specialized brain capillary endothelial cells building brain capillary walls.…”
mentioning
confidence: 99%
“…This work reports the first analysis of PAMAM dendrimers using this combined approach. The results provide important insights into strategies for developing nanoparticle systems for brain drug delivery 38 .…”
Section: Dendrimers In Cns Drug Deliverymentioning
confidence: 96%
“…For example, PAMAM dendrimers have been shown to be haemolytic and cytotoxic [98]. Some research results also showed that biotinylated PAMAM dendrimers may prove to be more toxic compared to PAMAM dendrimers alone [99]. The versatility of nanoemulsions is based on the different types of oils and surface modifiers that can be used [101].…”
Section: Dendrimersmentioning
confidence: 99%